Substitution position modulating the photophysical properties of anthracene derivatives based on Tröger's base. Issue 36 (6th September 2018) - Xu, Liang; Li, Yexin; Yan, Xiangzhen; Yuan, Chunxue
Abstract: Three different positional isomers based on Tröger's Base (TB) and anthracene were synthesized by Sonogashira coupling reaction and their optical, structural and electronic properties were compared. It is revealed that changing the substitution position of anthracene units on TB alters the optical and structural properties significantly. All of them are highly emissive in solutions, but when comes to solid state 2, 8- bis (anthracen-2-ylethynyl)- 6H, 12H -5, 11-methanodibenzo[ b, f ][1, 5]diazocine (TBAN2 ) shows aggregation-caused quenching quality while 2, 8- bis (anthracen-9-ylethynyl)- 6H, 12H -5, 11-methanodibenzo[ b, f ][1, 5]diazocine (TBAN1 ) and 2, 8- bis (anthracen-1-ylethynyl)- 6H, 12H -5, 11-methanodibenzo[ b, f ][1, 5]diazocine (TBAN3 ) are still emissive. It is obvious that changing substitution positions has a marked influence on their luminescence properties. Graphical abstract: The change in the substitution positions lead to different optical properties. Image 1